2015
DOI: 10.1007/s00415-015-7929-7
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of gray matter atrophy in Parkinson’s disease differs in cortical and subcortical regions

Abstract: Background Cortical and subcortical gray matter (GM) atrophy may progress differently during the course of Parkinson's disease (PD). We delineated and compared the longitudinal pattern of these PD-related changes. Methods Structural MRIs and clinical measures were obtained from 76 PD with different disease durations and 70 Controls at baseline, 18- and 36-months. Both cortical and subcortical (putamen, caudate, and globus pallidus) GM volumes were obtained, compared, and associated with PD clinical measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 38 publications
12
56
0
Order By: Relevance
“…Gray matter atrophy in PD has been reported by a number of groups (Hwang et al, 2013; Ibarretxe-Bilbao et al, 2012; Lewis et al, 2016; Pereira et al, 2014; Ramirez-Ruiz et al, 2007; Segura et al, 2014; Song et al, 2011; Tinaz et al, 2011; Zhang et al, 2014), and the current study confirmed these findings in a longitudinal cohort. On the other hand, past research has yielded inconsistent results regarding the extent and nature of white matter involvement in PD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Gray matter atrophy in PD has been reported by a number of groups (Hwang et al, 2013; Ibarretxe-Bilbao et al, 2012; Lewis et al, 2016; Pereira et al, 2014; Ramirez-Ruiz et al, 2007; Segura et al, 2014; Song et al, 2011; Tinaz et al, 2011; Zhang et al, 2014), and the current study confirmed these findings in a longitudinal cohort. On the other hand, past research has yielded inconsistent results regarding the extent and nature of white matter involvement in PD.…”
Section: Discussionsupporting
confidence: 90%
“…Cortical volume, however, may be a useful measure to detect overall structural changes during aging or disease processes, since it is the combined property of thickness and surface area. Indeed, loss of cortical volume has been documented both in healthy aging (Abe et al, 2008; Storsve et al, 2014) and Parkinson’s disease (PD) (Lewis et al, 2016), although the underlying mechanisms might be different. In healthy aging, dendrite losses and/or shrinkage of larger neurons (Terry et al, 1987) may drive the changes in cortical volume, since the number of cortical neurons is thought to remain relatively constant (Bartzokis et al, 2001; Freeman et al, 2008; Jernigan et al, 2001; Scheibel et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Previous longitudinal studies using different imaging analysis have suggested that striatal atrophy occurs earlier in the disease process, while cortical GM loss is restricted to later stages, reduced overall gyrification, and bilaterally in the inferior parietal, postcentral, precentral, superior frontal, and supramarginal areas was present in patients with disease for less than 1 year, and the rate loss was accelerated as disease progressed (37). Although our subjects presented some homogeneity in their mean clinical scale scores per group (with lower scores in the mild group, intermediate in the moderate group, and higher scores in the severe group in the motor and non-motor scales), we classified them solely based on their HY score.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic and clinical characteristics, the Movement Disorder Society Unified PD Rating Scale parts I, II, and III (MDS‐UPDRS‐I, ‐II, ‐III); levodopa‐equivalent daily dosage (LEDD); the Montreal Cognitive Assessment (MoCA); the Hamilton Depression Rating Scale (HDRS); and the PD Questionnaire (PDQ‐39) were obtained from all participants every 6 months, while patients were on optimized antiparkinsonian medications (ON state). PD subgroups (early‐stage PD [PDE], < 1 year; middle‐stage PD [PDM], < 5 years; and later‐stage PD [PDL], > 5 years) were created based on time after first documented Parkinson's disease diagnosis, as done previously . Detailed demographic data (for PD subgroups at the baseline and follow‐up visits) are provided in Supplementary Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…PD subgroups (early-stage PD [PDE], < 1 year; middlestage PD [PDM], < 5 years; and later-stage PD [PDL], > 5 years) were created based on time after first documented Parkinson's disease diagnosis, as done previously. 29 Detailed demographic data (for PD subgroups at the baseline and follow-up visits) are provided in Supplementary Table 1. All participants gave written informed consent that was in accordance with the Declaration of Helsinki and approved by the Penn State Hershey Institutional Review Board.…”
Section: Subjectsmentioning
confidence: 99%